Prevalence of Wheezing and Associated Risk Factors Among Infants in Recife, Pernambuco State, Brazil [Prevalência de Sibilância E Fatores de Risco Associados Em Crianças No Primeiro Ano de Vida, Residentes No Município de Recife, Pernambuco, Brasil] - Mallol-Villablanca, E (2011)
The aim of this study was to verify the prevalence of wheezing in infants (< 1 year of age) in Recife, Pernambuco State, Brazil, and to identify associated risk factors. Sample and methods: the study was performed according to the protocol of the International Study of Wheezing in Infants (EISL) in children ranging from 12 to 15 months of age. The sample was analyzed for presence or absence of wheezing. A total of 1,071 parents of children ranging from 12 to 15 months of age were interviewed. Prevalence of wheezing in the first year of life was 43%, with no difference between the sexes. Wheezing in the first year of life was associated with pneumonia, family history of asthma, more than nine episodes of upper airway infection, and the first cold before six months of age (p < 0.001). Prevalence of wheezing in the first year of life was high in Recife. Early onset (and high number) of colds, family history of asthma, and pneumonia were associated with wheezing in these children.